2006
DOI: 10.1089/acm.2006.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species—(ROS) Pathogens or Sources of Vital Energy? Part 1. ROS in Normal and Pathologic Physiology of Living Systems

Abstract: Free radicals and reactive oxygen species (ROS) are considered to be dangerous pathogens as they may damage key molecular constituents of cells. However this concept approach does not take into account vital functions of ROS in normal physiology. Information has emerged that a substantial share of oxygen consumed by aerobic organisms is used for ROS production and that ROS are indispensable for regulation of multiple functions of living cells. Yet, each cell is equipped with powerful means to eliminate ROS imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Recent estimations have shown that in adults >15% of oxygen consumed is turned into ROS under resting conditions and much more when their activity is high [8]. The process of one-electron oxygen reduction, in which energy of electronic excitation is generated, continuously occurs in human blood [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimations have shown that in adults >15% of oxygen consumed is turned into ROS under resting conditions and much more when their activity is high [8]. The process of one-electron oxygen reduction, in which energy of electronic excitation is generated, continuously occurs in human blood [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, besides the negative effects, ROS are also actively produced and required for many physiological functions in cells (Stone and Yang, 2006;Voeikov, 2006). In addition to the role of ROS in pathogen killing and angiogenesis (Segal, 2005;Ushio-Fukai, 2006), the production of ROS has also been reported to be important in cellular stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…But in the last forty years, evidences indicated increasingly Janus-faced behaviors of this element1-3 for the following reasons: Under certain conditions, oxygen may produce reactive species, even free radicals responsible for different molecular cell response like cellular stress4,5. Despite all undesired consequences provoked by these oxygen's properties, these facts were not yet in the focus of the scientific discussion and still poorly understood during the last few years as illustrated comprehensively6.…”
Section: Introductionmentioning
confidence: 99%